Metabolomics study of fibroblasts damaged by UVB and BaP - Xiaoyu Yang (Nature Portfolio, 2021)
Abstract We have recently shown that both UVB and BaP can induce the production of ROS, apoptosis and even cancer. However, the differences in the metabolic profiles of skin damaged by UVB, BaP or UVB combined with BaP have not been studied. Therefore, we examined the metabolic changes in the human foreskin fibroblast injured by UVB or BaP or the combination of the two, using ultra performance liquid chromatography (UPLC) coupled with quadrupole time-of-flight mass spectrometry (qTOF-MS). 24 metabolites were altered in the UVB damage group, 25 in the BaP damage group, and 33 in the UVB combined with BaP group. These alterations indicated that the metabolic mechanisms of HFF-1 cells treated with UVB or BaP are related to multiple main metabolites including glycerophosphocholine (PC), lactosylceramide (LacCer), guanidinosuccinic acid (GSA), glutathione(GSH), and lysophosphatidylcholine (LysoPC) and the main mechanisms involved glycerophospholipid and glutathione metabolism. Thus, our report provided useful insight into the underlying mechanisms of UVB and BaP damage to skin cells.